Survey of neuroimaging in neurological surgery, current state, and emerging research - Narasimhan, Saramati; González, Hernán F. J. (Frontiers in Neuroimaging, 2023)
Neuroimaging plays a crucial role in enabling a surgeon's proficiency and achieving optimal outcomes across various subspecialties of neurosurgery. Since Wilhelm Roentgen's groundbreaking discovery of the radiograph in 1895, imaging capabilities have advanced astronomically, significantly benefiting the field of neurosurgery. In this review, we aim to provide a concise overview of neuroimaging in four specific subspecialties: neuro-oncology, cerebrovascular, spine, and functional neurosurgery. Although the diseases and procedures mentioned are not exhaustive, they are illustrative examples of how neuroimaging has contributed to advancements in neurosurgery. Our intention is to emphasize the critical role of neuroimaging in pre-operative, intra-operative, and post-operative settings, while also highlighting its potential to drive research to further enhance existing neurosurgical technologies and ultimately better patient outcomes.